EFEKTIvITas PELaTIHaN PENGaMBILaN KEPUTUsaN KaRIER MELaLUI KELOMPOK PsIKOEDUKasI DI sMaN 1 MaDIUN - Ali, Muhammad (IAIN Ponorogo, 2015)
Abstract: Career decision-making is an important task for teenagers, but not all teenagers were able to pass this task successfully, this condition is known in the theory of career indecision. This research aims to reduce the inability of the student career decision-making in the form of career decision-making training through psychoeducation group. For the purpose of this study was designed using Solomon Four Group. Population is all students of class X SMAN 1 Madiun. This research data analysis using independent sample t test with a level of 95%. The results showed that the career decision-making training through psychoeducation group can reducing the level of student career indecision.Â .ØØ§Ø¬ÙØ¨ Ø©ÙÙØ¸ÙÙØ§ ÙØ°ÙØ¨ Ù Ø§ÙÙÙØ§ ÙÙØ¹ ÙÙØ±Ø¯Ø§Ù Ø¹ÙÙ ÙØ¬Ø§ Ø³ÙÙ ÙÙÙ ØØ¨Ø§Ø¨Ø´ÙÙ Ø©Ù Ø§Ù Ø©ÙÙØ¸Ù ÙÙÙ Ø¹ÙØ§ Ø±Ø§Ø±ÙÙØ§ Ø°Ø§ ÙØ® ØªØ§ ÙØ§ÙÂ ÙÙÙÙØª Ø©Ø³Ø§Ø±Ø¯ÙØ§ ÙØ°Ù ØªÙØ¯ÙØªØ³Ø§ .ÙÙÙ Ø¹ÙØ§ Ø±Ø§Ø±ÙÙØ§ Ø°Ø§ØªØ§ ÙÙØ¹ Ø©Ø±Ø¯ÙÙØ§ Ù Ø¯Ø¹Ø¨ â ÙÙ Ø¹ÙØ§ Ø©ÙØ±Ø¸Ù ÙÙ â Ø¹ÙØ§ÙÙØ§ Ø§Ø°Ù ÙÙØ® Ø³Ù Â ÙÙØ±Ø· ÙØ¹ ÙØ§ÙÙ Ø¬Ø§ Ø§Ø°Ù ÙÙ Ø©ÙØ¨ÙØ±Ø¯ØªÙØ§ Ø©Ø±ÙØ¯ÙØ§ ÙÙØ´ ÙÙ Ø¨ÙØ§Ø·ÙØ§ ÙØ¯Ù ÙÙÙ Ø¹ÙØ§ Ø±Ø§Ø±ÙÙØ§ Ø°Ø§ØªØ§ ÙÙØ¹ Ø©Ø±Ø¯ÙÙØ§ Ù Ø¯Ø¹ Ø¹Ø¶ÙÂ Ø¨ÙØ§Ø·ÙØ§ Ø¹ÙÙ Ø¬Ù Ø«ØØ¨ÙØ§ Ø©ÙÙØ¹ Ø§Ù Ø£ .Â Â Ø¨ Ø«ØØ¨ÙØ§ Ø§Ø°Ù Ù ÙØ® Ù Øµ ÙÙØ·ÙÙÙ Ø§ Ø§Ø°ÙØ¨ .ÙÙØ¨ØªØ±Ø³ÙÙÙØ§ Ø©ÙØ±ÙÂ ÙØ¯ØµÙØ§ ÙÙØªØ³Ø¨Ù Â ÙØ® ÙÙØªØ³ÙÙ Ø§Â ÙØ® ÙØºØªÙÙ Ø§Â Ø±Ø§Ø¨ØªØ®Ø§Ø¨Ù ØªØ§ÙØ§ÙØ¨ÙØ§ ÙÙÙØªØ Ø§Ù Ø£ .Â Ø±Ø´Ø§Ø¹ÙØ§ ÙØµÙØ§ ÙÙÂ Ø¶ÙÙØª ÙÙ Ø±Ø«Ø¤Øª ÙÙØ¨ØªØ±Ø³ÙÙÙØ§ Ø©ÙØ±ÙØ¨ ÙÙÙ Ø¹ÙØ§ Ø±Ø§Ø±ÙÙØ§ Ø°Ø§ØªØ§ ÙØ¹ Ø©ÙØ¨ÙØ±Ø¯ØªÙØ§ Ø©Ø±ÙØ¯ÙØ§ ÙØ£ ÙÙØ¹ Ø«ØØ¨ÙØ§ Ø¬Ø¦Ø§ØªÙ ØªÙØ¯ ..Ø¨ÙØ§Ø·ÙØ§ ÙØ¯Ù ÙÙÙ Ø¹ÙØ§ Ø±Ø§Ø±ÙÙØ§ Ø°Ø§ØªØ§ ÙÙØ¹ Ø©Ø±Ø¯ÙÙØ§ Ù Ø¯Ø¹ ÙÙØªØ³ÙÙ Ø§